Quantitative analysis of the expression of p53 gene in colorectal carcinoma by using real-time PCR - Bong, Ivyna Pau Ni; Lim, Patricia; Balraj, Pauline; Sim, Edmund U. H.; Zubaidah, Zakaria (Malaysian Society of Parasitology and Tropical Medicine, 2006)
Colorectal carcinoma ranks third among ten leading causes of cancer in Malaysia. The colorectal carcinoma tumourigenesis involves the inactivation of tumour suppressor genes, and activation of proto-oncogenes. The p53 is one of the tumour suppressor genes that is involved in the colorectal carcinogenesis. The p53 gene is located on human chromosome 17p13.1 and comprises of 11 exons. Deficiencies in the p53 gene can cause the cancerous cells to spread to distant organs such as liver, lungs, lymph nodes, spine and bone. The most common p53 abnormalities that can lead to the metastasis of colorectal tumours are mutation and deregulation of the gene. In this study, nine colorectal carcinoma samples were used to establish a simple and sensitive strategy in the study on in vivo p53 expression by using realtime LightCycler SYBR Green I technology.